2020
DOI: 10.1038/s41598-020-69740-2
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting cancer-specific survival in patients with osteosarcoma as secondary malignancy

Abstract: The prognostic factors for survival among patients with secondary osteosarcoma remain unclear. The aim of this study was to develop a practical nomogram for predicting cancer-specific survival (CSS) in patients with osteosarcoma as a secondary malignancy. The surveillance, epidemiology, and end results database was used for the identification of osteosarcoma cases. The total sample comprised 5860 cases of primary osteosarcoma and 268 cases of secondary osteosarcoma during the period from 1973 to 2015. The CSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Nomogram, an easy-to-use comprehensive tool, which could incorporate the conducive factors together, is of great significance for clinicians to accurately clarify diagnosis and predict survival of individual patient. [17][18][19][20] As for patients with osteosarcoma, several predictive models have been constructed in previous studies, 6,11,13 however, limited data is available for this special age group. Besides, independent predictors for OS and CSS in elderly patients with osteosarcoma are still controversial until now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nomogram, an easy-to-use comprehensive tool, which could incorporate the conducive factors together, is of great significance for clinicians to accurately clarify diagnosis and predict survival of individual patient. [17][18][19][20] As for patients with osteosarcoma, several predictive models have been constructed in previous studies, 6,11,13 however, limited data is available for this special age group. Besides, independent predictors for OS and CSS in elderly patients with osteosarcoma are still controversial until now.…”
Section: Discussionmentioning
confidence: 99%
“…10 In recent years, this model has been widely applied as the increased need of individualized medicine in a great variety of malignant tumors as well as in patients with different types of osteosarcoma. [11][12][13][14][15] Since different clinical and prognosis features between two age groups, no study is available to develop a prognostic nomogram for osteosarcoma in elderly patients. Therefore, in this study, we aimed to construct and verify a survival nomogram integrating the accessible clinical features to improve prognostication for elderly patients osteosarcoma in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, nomograms are known tools to help patients and physicians make important treatment decisions. Based on information collected from thousands of patients, this tool can be used to predict cancer-specific survival [128] or assess risk based on patient-specific characteristics and tumour evolution [129]. Although they provide excellent graphical depictions, nomograms are limited in terms of capturing a large number of variables and their interactions in predictive models [130].…”
Section: Instantiations Of Learning Mechanistic Interaction Networkmentioning
confidence: 99%
“…The Surveillance, Epidemiology, and End Results (SEER) database is an authoritative cancer statistics database in the United States that records morbidity, mortality, and incidence information for millions of patients with malignancies. Currently, although there have been relevant studies on osteosarcoma based on the SEER database, these prediction models showed a lower power (almost AUC < 0.8) or have no external data validation ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%